An Application of Curvilinear Break-Even Analysis. - Givens, Horace E. (The Accounting Review, 1966)
Abstract Curvilinear break-even analysis is made more meaningful to accounting student if analytical and mathematical procedures used can be related to a simulated real world situation. To do this it is necessary to ascertain cost and revenue data of a non-linear character, and then to derive cost and revenue equations that will form the basis of mathematical analysis. The article illustrates the derivation of such equations and their subsequent use. A benefit in presenting such an example to students is that those whose mathematical background is weak often gain a greater insight into the concept of the derivative and its applications to real world situations. Caution should be exercised in discussing results of any mathematical analysis involving cost and revenue data. The complexity of the mathematical process often tends to imply a greater precision than actually exists. No accounting or mathematical results can be better than the raw data used. If that data has been determined by subjective judgments as may be the case with cost and revenue information, results cannot be invalidated.